Climate Change and Monsoon: Looking Into Its Antecedents - Gawali, Praveen B.; Lakshmi, B.V.; Deenadayalan, K. (My University, 2019)
Climate change is a tricky issue. The Indian subcontinent has experienced many regional and local climatic changes in its past. There is overwhelming geological evidence of global climatic changes which are associated with extinctions and new life form adaptations. The Indian subcontinent is governed by monsoonal precipitation inextricably linked with the socioeconomic conditions of its citizenry. The subcontinent has a long coastline which is prone to sea level changes having potential to displace millions of people. The agriculture, dependent on the monsoonal precipitation, is already showing signs of disarray. Floods and droughts have been visiting regions that were hitherto immune to these hazards. The fast-eroding green cover and forests has unleashed extinctions of life forms that are so vital to the well-being of the environment. In climate change dynamics, many variables, and not a single one, have a role to play. Humans have the capacity to tackle this situation, and all the nations need to come together to fight the menace of climate change, that is part natural and part man-made. The technological innovations are long overdue to mitigate the hazards faced.
Keywords: Climate change; Sea level; Indian subcontinent; Magnetic susceptibility; environmental